2020
DOI: 10.1101/2020.06.30.180513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leptin suppresses development of GLP-1 Inputs to the Paraventricular Nucleus of the Hypothalamus

Abstract: AbstractThe nucleus of the solitary tract is critical for the central integration of signals from visceral organs and contains preproglucagon (PPG) neurons, which express leptin receptors and send direct projections to the paraventricular nucleus of the hypothalamus (PVH). Here, we visualized neuronal projections of PPG neurons in leptin-deficient Lepob/ob mice and found that projections from PPG neurons are elevated compared with controls, and PPG projecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, long-term sucrose consumption reduced impulse control in the novelty-suppressed feeding, and this was not observed when sucrose access was restricted. Although novelty-suppressed feeding test is primarily to assess anxiety-like behaviors, studies have shown that a reduced latency to feed could be correlated with augmented food seeking and increased meal size ( Biddinger et al, 2020 ), increased hunger and reduced-feeding control after fasting ( Burghardt et al, 2016 ), and together with hyperlocomotion, increased motor impulsivity ( Bevilacqua et al, 2010 ; Angoa-Pérez et al, 2014 ; Piggott et al, 2020 ). This suggests that the reduced latency to feed we observed after long-term sucrose intake could be the result of impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, long-term sucrose consumption reduced impulse control in the novelty-suppressed feeding, and this was not observed when sucrose access was restricted. Although novelty-suppressed feeding test is primarily to assess anxiety-like behaviors, studies have shown that a reduced latency to feed could be correlated with augmented food seeking and increased meal size ( Biddinger et al, 2020 ), increased hunger and reduced-feeding control after fasting ( Burghardt et al, 2016 ), and together with hyperlocomotion, increased motor impulsivity ( Bevilacqua et al, 2010 ; Angoa-Pérez et al, 2014 ; Piggott et al, 2020 ). This suggests that the reduced latency to feed we observed after long-term sucrose intake could be the result of impulsivity.…”
Section: Discussionmentioning
confidence: 99%